Muromec, brjanec i poločanin v Lukke: ob izvestnych i novonajdennych drevnerusskich nadlisjach na stenach sobora sv. Martina - Micheev, Savva Michajlovič (Studi slavistici, 2023)
In the 1970s, four Cyrillic inscriptions were discovered on the walls of St. Martin Cathedral in Lucca. They are etched on a marble block reused as an architrave in the 13th century. Two texts, including one deeply embedded and noticeable inscription, were first identified as Old Russian, while another was attributed to a speaker of a dialect of Serbo-Croatian. - This article gives a new edition of the inscriptions on the architrave, with a revised reading. In particular, the inscription that had been considered Serbo-Croatian was ascertained to be an autograph of a pilgrim from Briansk. The presence on the architrave of three graffiti indicating the travelers’ cities of origin, namely Murom, Briansk, and Polotsk, testifies to this group of inscriptions having been left by pilgrims travelling as an organized group. - Three other brief Cyrillic graffiti were discovered recently on a marble block of the portico of the same cathedral. The photographic images of these three graffiti are also published in this article. - The paleography, orthography, language and location of the inscriptions indicate that they were left by pilgrims who came from Rus in the 12th or early 13th century.
Online veröffentlicht: 29. Januar 2024
Gesehen am 15.05.2025